Authenticity, Craftsmanship, and Character in the Artworks of Grayson Perry - Hemingway, Christine A. (Business ethics quarterly, 2024)
Authenticity, Craftsmanship, and Character in the Artworks of Grayson Perry - Volume 34 Issue 4